Modelos termo-hidráulicos para diferentes sistemas de arrefecimento de transformadores de potência - Oliveira, Micael Márcio (2024)
In the context of electrical power systems, transformers have great systemic importance, since they are responsible for processing high levels of energy. Since the internal temperatures are a factor that significantly influences its deterioration, the determination of these temperatures and the performance of the cooling systems is necessary. In this context, this work applies a new modeling approach based on the distribution of total flow in networks of hydraulic resistances to construct thermal-hydraulic (TH) models for various configurations of power transformer cooling systems, focusing on heat dissipation to the environment. Based on the theoretical foundations of heat transfer, the TH models encompass the active part, tank, and radiators, with subsequent coupling through algorithms developed in a programming environment. The thermal resistance networks of the radiators include heat transfer modes at all stages, along with an additional model of a heat exchanger. For each cooling system operating mode, the algorithm iteratively solves the inlet and outlet temperatures of the radiator or heat exchanger, in addition to determining the temperatures at various points and the heat transferred to the environment in each section. For results validation, temperature rise tests were carried out in a prototype transformer and for the heat exchanger, the comparison was performed with design data and simulations using computational fluid dynamics (CFD). The results demonstrate a satisfactory level of assertiveness for the ODAN, ODAF, ONAN, and ONAF TH models configurations, using experimental correlation for air forced. In the OFAN and OFAF modes, the models display greater discrepancies, not representing the non-homogeneous flow inside the tank, which was additionally verified through CFD simulations, requiring further studies of the flow inside the tank in the OF mode. Furthermore, for the ODWF configuration, the results for the heat exchanger TH model showed minor discrepancies with the design data, still indicating good performance when the ODWF model is executed with operational parameters of a real large power transformer. The TH models also serve as an important tool for monitoring and, particularly, for optimizing designs, allowing analysis of the impact of physical modifications on transformers thermal behavior.